Static Fluid Sphere with Pressure Equal to Energy Density: Solution to Einstein's Field Equation with Stiff Matter Equation of State (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This research paper provides solution of Einstein’s field equation with special equation of state i.e. Stiff matter) To overcome the difficulty of infinite density at the centre, it is assumed that the distribution has a core of radius r0 and constant density 0 which is surrounded by the fluid with pressure equal to energy density.